2004
DOI: 10.1111/j.1523-1755.2004.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

A new mutation (intron 9 +1 G>T) in the SLC12A3 gene is linked to Gitelman syndrome in Gypsies

Abstract: Demonstration of a novel point mutation within the SLC12A3 gene in our cohort of Gypsy families with Gitelman syndrome is highly suggestive of a founder effect. This finding will facilitate the identification of the genetic defect in further cases of Gitelman syndrome among the Gypsy population. Our study represents the largest series ever published of patients with Gitelman syndrome having the same underlying mutation, and supports the lack of correlation between genotype and clinical phenotype in this diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…They were mainly found in heterozygous compound subjects, except for c.1180 ϩ 1GϾT, which is highly prevalent in the Gypsy population. 17 In the entire set of 172 point mutations, 100 have not been described before (53 missense, 19 frameshift, 16 splice, 6 nonsense, and 6 in-frame mutations; Supplementary Table 1, A-C). Supplementary Table 2 sums up the novel missense mutations and their in silico predictions.…”
Section: Results Of the First Screen By Direct Sequencing Analysismentioning
confidence: 99%
“…They were mainly found in heterozygous compound subjects, except for c.1180 ϩ 1GϾT, which is highly prevalent in the Gypsy population. 17 In the entire set of 172 point mutations, 100 have not been described before (53 missense, 19 frameshift, 16 splice, 6 nonsense, and 6 in-frame mutations; Supplementary Table 1, A-C). Supplementary Table 2 sums up the novel missense mutations and their in silico predictions.…”
Section: Results Of the First Screen By Direct Sequencing Analysismentioning
confidence: 99%
“…Finally, in 7% of patients, three or more mutations occur. Only one study, in 20 patients from 12 different European families who were of Gypsy origin, revealed the same mutation in all patients (64). All these patients were homozygous for a substitution of G for T in the first position of intron 9, affecting consensus donor splice site motif and resulting in a nonsense protein.…”
Section: A Gitelman's Diseasementioning
confidence: 99%
“…ac.uk/uwcm/mg/hgmd0.html). There are ϳ100 different mutations spread throughout the SLC12A3 gene, from the amino-to the carboxy-terminal domain of TSC, without preference for a particular location along the protein (55, 64,67,241,245,259,264,271,281,307,339,377,395,396,398,442,449). Figure 21 illustrates the proposed TSC secondary structure and location of the majority of reported mutations.…”
Section: A Gitelman's Diseasementioning
confidence: 99%
“…Growth impairment is frequently described in Bartter's syndrome (22). Gitelman's syndrome, traditionally considered as asymptomatic or responsible for mild clinical manifestations (9), has been reported to be accompanied by short stature in over 30% of children (8).…”
mentioning
confidence: 99%